Pengembangan Ternak Ayam Kampung Melalui Penerapan Teknologi Inseminasi Buatan dan Pemanfaatan Pakan Lokal di Kota Kendari - Asminaya, Nur Santy; Tasse, Andi Murlina; Sandiah, Natsir; Nuraini, Nuraini; Badaruddin, Rusli; Indi, Amiludin; Napirah, Astriana; Hadini, Hairil Azulyatno; Salido, Wa Laili (IGKOJEI: Jurnal Pengabdian Masyarakat, 2021)
ABSTRACT The supply DOC of super free-range chicken in Southeast Sulawesi until now still comes from outside. This causes the DOC price to be quite high due to the high cost of transportation in the distribution process. In addition, the pandemic period also made the situation more difficult to obtain DOC from outside which had an impact on the lack of supply of super free-range chicken. Therefore, it is necessary to independently procure a source of DOC for free-range chicken. This community service aims to provide a source of information and training in the use of AI technology and the use of feed based on local feed ingredients to the community through the FPT-UHO Village Development Program. This service is carried out in a group of native chicken farmers in Mokoau Village, Kambu sub-district, Kendari City by involving various components such as community leaders, youth and government officials. This activity is carried out by means of online and offline presentations and training. The results obtained in this service are in the form of DOC (according to standards), free-range chickens that have a high body weight, free-range chicken feed based on local feed resources, scientific articles and theses. Based on the results of this activity, it can be concluded that the FPT-UHO village development program is able to improve the ability of farmers to utilize AI technology and feed processing technology based on local feed ingredients. Keywords: DOC; feed; Livestock; Super free-range chicken; Technology ABSTRAK Pasokan DOC ayam kampung super di Sulawesi Tenggara hingga saat ini masih berasal dari luar. Hal ini mengakibatkan harga DOC cukup tinggi karena mahalnya biaya transportasi dalam proses ditribusinya. Selain itu masa pandemi juga menjadikan situasi lebih sulit untuk memperoleh DOC dari luar yang berdampak pada kurangnya pasokan daging ayam kampung super. Oleh karena itu, perlu adanya pengadaan sumber DOC ayam kampung secara mandiri. Pengabdian kepada masyarakat ini bertujuan untuk memberikan sumber informasi dan pelatihan dalam pemanfaatan teknologi IB dan pemanfaatan pakan berbasis bahan pakan lokal kepada masyarakat melalui Program Bina Desa FPT-UHO. Pengabdian ini dilakukan di kelompok peternak ayam kampung di Kelurahan Mokoau, kecamatan Kambu, Kota Kendari dengan melibatkan berbagai komponen seperti tokoh masyarakat, pemuda dan aparat pemerintah. Kegiatan ini dilakukan dengan cara persentasi dan pelatihan secara daring dan luring. Hasil yang diperoleh dalam pengabdian ini berupa DOC (sesuai dengan standar), ayam kampung yang memiliki bobot badan yang tinggi, pakan ayam kampung berbasis sumber daya pakan lokal, artikel ilmiah dan skripsi. Berdasarkan hasil kegian ini, dapat disimpulkan bahwa program bina desa FPT-UHO mampu meningkatkan kemampuan peternak untuk memanfaatkan teknologi IB dan teknologi pengolahan pakan berbasis bahan pakan lokal. Kata kunci: Ayam kampung super; DOC; Pakan; Teknologi; Ternak